The influence of ballroom dancing on the formation of emotional resilience - Rebrikova, Tatiana (Global Prosperity, 2025)
Abstract. The article focuses on examining the impact of ballroom dancing on the process of developing emotional resilience in children and adolescents. The aim of the study is to explore how ballroom dancing contributes to the formation of emotional resilience in children and teenagers as a dynamic process of mobilizing internal and external resources in response to stressful situations. The research employed general scientific methods of cognition, including analysis, synthesis, comparison, generalization, and systematization of academic sources. The findings indicate that in modern science, emotional resilience is viewed as a complex and dynamic process based on the mobilization of personal resources when facing crises or stressful circumstances. It has been proven that its development depends on numerous factors, among which empathy, social support, anxiety levels, emotional regulation, cognitive flexibility, and self-confidence play a central role. Together, these characteristics form a foundation for restoring inner balance and adapting successfully to changing social and cultural conditions. The study highlights that ballroom dancing exerts a multidirectional positive effect on key aspects of emotional resilience. Its effectiveness is explained by biological mechanisms (endorphin and oxytocin release), psychological factors (flow state, fulfillment of basic needs for competence and self-expression), and sociocultural components (group support, collective cohesion). Regular participation in ballroom dancing has been shown to reduce social anxiety, enhance empathy, improve physical fitness, and foster a positive body image. The practical significance of the study lies in the fact that its results can be applied in pedagogical, psychological, and sociocultural practices to strengthen emotional resilience in children and adolescents through ballroom dancing.